Hubungan Antara Tingkat Kecemasan Dengan Kejadian Insomnia Menjelang Ujian Sooca Pada Mahasiswa Tingkat I Fk Unisba Tahun 2022 - Audia Rizky Pratama; Siska Nia Irasanti; Rika Nilapsari (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Anxiety, an emotional response to uncertainty, often involves feelings of fear and physical symptoms. Insomnia, difficulty sleeping linked to mental health issues. SOOCA exam, an oral case analysis for medical students, tends to increase anxiety and sleep problems. This research aims to determine the anxiety levels and incidence of insomnia among FK UNISBA 2022 students and analyze the relationship between them. The study used an analytical observational method with a cross-sectional design. The research subjects were students of the Medical Education study program at FK UNISBA, class of 2022, selected through simple random sampling. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire for anxiety levels and the Insomnia Severity Index (ISI) for measuring insomnia incidence. Data analysis involved univariate and bivariate tests. Out of 35 respondents, 28.7% of students experienced anxiety before the SOOCA exam. Out of 95 respondents, 77.9% experienced insomnia. Statistical analysis showed a significant relationship between anxiety levels and insomnia incidence in FK UNISBA students in the first year of 2022 (p = 0.044 <0.05). This finding illustrates that the SOOCA exam can cause anxiety and insomnia among medical students. The SOOCA exam at FK Unisba triggers anxiety among medical students. This oral exam situation increases anxiety and sleep problems. The experience of a new role and the Problem-Based Learning (PBL) system also contribute to the anxiety of first-year students. Recommendations for future research include expanding the sample, a longitudinal research approach, and exploring additional factors influencing the relationship between anxiety and insomnia in students. It is also suggested to consider implementing student welfare programs focusing on stress management, counseling, and holistic support in the academic environment. Abstrak. Kecemasan, respons emosional terhadap ketidakpastian, seringkali melibatkan perasaan ketakutan dan gejala fisik. Insomnia, kesulitan tidur yang terkait dengan masalah kejiwaan. Ujian SOOCA, ujian lisan menganalisis kasus pada mahasiswa kedokteran, cenderung meningkatkan kecemasan dan masalah tidur. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan dan kejadian insomnia Mahasiswa FK UNISBA 2022 serta menganalisis hubungan antara keduanya. Penelitian menggunakan metode observasional analitik dengan desain cross-sectional. Subjek penelitian adalah mahasiswa program studi Pendidikan Kedokteran FK UNISBA angkatan 2022, dipilih melalui simple random sampling. Data dikumpulkan dengan kuesioner Hamilton Anxiety rating Scale (HARS) untuk mengukur tingkat kecemasan dan Insomnia Severity Index (ISI) untuk mengukur kejadian insomnia. Analisis data melibatkan uji univariat dan bivariat. Dari 35 orang responden, didapatkan 28,7% mahasiswa mengalami kecemasan menjelang ujian SOOCA. Dari 95 orang responden, didapatkan 77,9% mengalami insomnia. Analisis statistik menunjukkan adanya hubungan signifikan antara tingkat kecemasan dan kejadian insomnia pada mahasiswa FK UNISBA tingkat I tahun 2022 (p = 0,0440<05). Temuan ini memberikan gambaran bahwa ujian SOOCA dapat menyebabkan kecemasan dan kejadian insomnia pada mahasiswa kedokteran. Ujian SOOCA di FK Unisba, menjadi pemicu kecemasan pada mahasiswa kedokteran. Situasi ujian lisan ini meningkatkan kecemasan dan masalah tidur. Pengalaman peran baru dan sistem PBL juga berkontribusi pada kecemasan mahasiswa tingkat satu. Saran untuk penelitian berikutnya melibatkan perluasan sampel, pendekatan penelitian longitudinal, dan eksplorasi faktor tambahan yang memengaruhi hubungan antara kecemasan dan insomnia pada mahasiswa. Disarankan juga mempertimbangkan implementasi program kesejahteraan mahasiswa dengan fokus pada manajemen stres, konseling, dan dukungan holistik di lingkungan akademik.